2014
DOI: 10.1016/j.jjcc.2014.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Impact of clustered depression and anxiety on mortality and rehospitalization in patients with heart failure

Abstract: Our results showed that clustered depression and anxiety were associated with worse outcomes in patients with HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 60 publications
4
40
1
7
Order By: Relevance
“…Prior studies found that depression increased the risk of hospitalisation in HF patients. Consistent with these studies (Howie-Esquivel & Spicer, 2012; Kato et al, 2009;Suzuki et al, 2014;Wen et al, 2014), the present study also revealed that HF patients in the rehospitalisation group had higher scores for depressive symptoms than their peers in the non-rehospitalisation group during the six-month follow-up, and the risk of hospital admission was 2.239 times higher for HF patients with depressive symptoms than for those without depressive symptoms. HF patients with depression may feel disappointed, incapable of preventing illness recurrences and hopeless about their future (Wen et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Prior studies found that depression increased the risk of hospitalisation in HF patients. Consistent with these studies (Howie-Esquivel & Spicer, 2012; Kato et al, 2009;Suzuki et al, 2014;Wen et al, 2014), the present study also revealed that HF patients in the rehospitalisation group had higher scores for depressive symptoms than their peers in the non-rehospitalisation group during the six-month follow-up, and the risk of hospital admission was 2.239 times higher for HF patients with depressive symptoms than for those without depressive symptoms. HF patients with depression may feel disappointed, incapable of preventing illness recurrences and hopeless about their future (Wen et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Among the psychological factors, depression was found to be an important determinant influencing rehospitalisation (Suzuki et al, 2014). Many studies showed that HF patients simultaneously experience depression; indeed, the prevalence of depression was reported to range from 15%-40% in HF patients in Western countries (Rutledge, Reis, Linke, Greenberg, & Mills, 2006;O'Connor et al, 2008;Alhurani et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety, but not depression significantly predicted self-care management scores. It is known that HF patients experience high levels of anxiety [29], but no data exist to describe anxiety in Hispanic patients with HF. Riegel and colleagues investigated the effect of a 6-month telephone case management program on hospital readmissions and depression in one of the few disease management studies that enrolled Hispanics of Mexican-American origin [30].…”
Section: Discussionmentioning
confidence: 99%
“…Suzuki et al [23] studied the effect of combined depression and anxiety on the mortality and readmissions in patients with HF. They included 221 patients with HF and based their study on an observation that depression and anxiety often coexist and may be a common factor impacting heart disease.…”
Section: Introductionmentioning
confidence: 99%